Detecting regions of homozygosity improves the diagnosis of pathogenic variants and uniparental disomy in pediatric patients. Issue 6 (23rd February 2022) - Wen, Jiadi; Chai, Hongyan; Grommisch, Brittany; DiAdamo, Autumn; Dykas, Daniel; Ma, Deqiong; Popa, Andreea; Zhao, Chen; Spencer‐Manzon, Michele; Jiang, Yong‐Hui; McGrath, James; Li, Peining; et al.
Abstract: Chromosomal microarray analysis using single nucleotide polymorphism probes can detect regions of homozygosity (ROH). This confers a potential utility in revealing autosomal recessive (AR) diseases and uniparental disomy (UPD). Results of genetic testing among pediatric patients from 2015 to 2019 were evaluated. Diagnostic findings with detected ROH from large consecutive case series in the literature were reviewed. Of 2050 pediatric patients, 65 (3%) had one or more ROH and 31 (53%) had follow‐up whole exome sequencing (WES) and methylation studies. Seven homozygous variants were detected and four of them from three patients (9.6%) were within the detected ROH and classified as pathogenic or likely pathogenic variants for AR diseases. One patient (3%) had segmental UPD15q for a diagnosis of Prader–Willi syndrome. Additive diagnostic yield from ROH reporting was at least 0.2% (4/2050) of pediatric patients. These results were consistent with findings from several large case series reported in the literature. Detecting ROH had an estimated baseline predictive value of 10% for AR diseases and 3% for UPD. Consanguinity revealed by multiple ROH was a strong predictor for AR diseases. These results provide evidence for genetic counseling and recommendation of follow‐up WES and methylation studies for pediatric patients reported with ROH.